Renal Stress Testing in the Assessment of Kidney Disease - Lakhmir S. Chawla; Claudio Ronco (Kidney International Reports, 2016)
As part of human evolutionary development, many human organ systems have innate mechanisms to adapt to increased “work demand” or stress. This reserve capacity can be informative and is used commonly in cardiology to assess cardiac function (e.g., treadmill test). Similarly, the kidney possesses reserve capacity, which can be demonstrated in at least 2 of the following renal domains: glomerular and tubular. When appropriate stimulants are used, healthy patients with intact kidneys can significantly increase their glomerular filtration rate and their tubular secretion. This approach has been used to develop diagnostics for the assessment of renal function. This article reviews both glomerular and tubular kidney stress tests and their respective diagnostic utility.